2011
DOI: 10.1007/8904_2011_50
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxyacyl-Coenzyme A Dehydrogenase Deficiency: Identification of a New Mutation Causing Hyperinsulinemic Hypoketotic Hypoglycemia, Altered Organic Acids and Acylcarnitines Concentrations

Abstract: The human HADH gene encodes the short-chain-L-3-hydroxyacyl-CoA dehydrogenase, the enzyme which catalyzes the third step of the b-oxidation of the fatty acids in the mitochondrial matrix. Loss-of-function mutations in the HADH gene lead to short-chain-L-3-hydroxyacyl-CoA dehydrogenase deficiency, an autosomal recessive genetic defect of unknown prevalence with a wide spectrum of phenotypic variability. As in other metabolic diseases, the diagnostic relevance of the biochemical evaluations, plasma acylcarnitine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…Of importance, for NBS programs using underivatized methods, hydroxy-C4-carnitine is isobaric to malonyl-carnitine (C3DC) and subsequently indistinguishable from this metabolite. Therefore, when underivatized methodology is used, it is necessary that follow-up for samples that screen positive for C3DC include confirmatory testing for both elevated malonyl-carnitine and hydroxy-C4-carnitine [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Of importance, for NBS programs using underivatized methods, hydroxy-C4-carnitine is isobaric to malonyl-carnitine (C3DC) and subsequently indistinguishable from this metabolite. Therefore, when underivatized methodology is used, it is necessary that follow-up for samples that screen positive for C3DC include confirmatory testing for both elevated malonyl-carnitine and hydroxy-C4-carnitine [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Also, peroxisomal β‐oxidation requires the carnitine shuttle into mitochondria, and it is known that interference with the shuttle in the peroxisome by loss of the peroxisomal acetyl transferase impairs growth on fatty acids and acetate in the fungal pathogen Sclerotinia sclerotiorum (Liberti et al ., ). A defect in the human hydroxyacyl‐coenzyme A dehydrogenase (HADH), a homologue to the Ustilago mitochondrial Had1 protein, leads to an over accumulation of C4‐OH acylcarnitine, suggesting an imbalance and improper usage of acylcarnitine in HADH deficient patients (Van Hove et al ., ; Popa et al ., ). The over‐accumulation of shorter and longer acyl‐carnitine derivates leads to a depletion of carnitine for transport of acyl and acetyl groups from the peroxisome.…”
Section: Discussionmentioning
confidence: 97%
“…Recessive mutations in the HADH gene were first described by Clayton et al ( 3 ) in a four-month-old infant with hypoketotic hypoglycemia, inappropriately elevated insulin levels and elevated blood spot hydroxybutyrylcarnitine concentration. Since then, another 36 patients have been reported with HADH mutations ( 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ). The clinical presentation of CHH due to HADH mutations is heterogeneous with some patients presenting with severe neonatal hypoglycemia and others - with mild infancy-onset hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Birth weight of patients with HADH gene mutation were usually reported as normal from 2730 g to 4350 g ( 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ). Early admitted patients usually had hypoglycemic seizure as our case ( 3 , 4 , 5 , 8 , 9 , 10 , 13 , 14 , 15 ). Martins et al ( 4 ) reported four new cases and reviewed seven reported cases with HH due to HADH deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation